2018
DOI: 10.1126/science.aar3394
|View full text |Cite
|
Sign up to set email alerts
|

Rapid change of superconductivity and electron-phonon coupling through critical doping in Bi-2212

Abstract: Electron-boson coupling plays a key role in superconductivity for many systems.However, in copper-based high-temperature (Tc) superconductors, its relation to superconductivity remains controversial despite strong spectroscopic fingerprints. Here we use angle-resolved photoemission spectroscopy to find a striking correlation between the superconducting gap and the bosonic coupling strength near the Brillouin zone boundary in Bi2Sr2CaCu2O8+δ. The bosonic coupling strength rapidly increases from the overdoped Fe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
86
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 54 publications
12
86
2
Order By: Relevance
“…In conventional superconductors, the EPC drives the formation of bosonic bound states of electrons (the Cooper pairs) [1]. In unconventional superconductors such as copper oxides (cuprates), the role of the EPC is lively discussed [2][3][4][5][6][7][8][9][10][11]. Though a purely phonon-mediated mechanism cannot account for the high critical temperatures observed in doped cuprates, the electron-lattice interaction may enhance pair binding when it operates in synergy with a dominant mechanism [12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…In conventional superconductors, the EPC drives the formation of bosonic bound states of electrons (the Cooper pairs) [1]. In unconventional superconductors such as copper oxides (cuprates), the role of the EPC is lively discussed [2][3][4][5][6][7][8][9][10][11]. Though a purely phonon-mediated mechanism cannot account for the high critical temperatures observed in doped cuprates, the electron-lattice interaction may enhance pair binding when it operates in synergy with a dominant mechanism [12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…Combining the electron energy shift and the lattice distortion defines a coherent "lock-in" experiment which determines the deformation potential purely experimentally [31]. Furthermore, improvements of the time resolution will grant access to other important modes, in particular the 8.5 THz B 1g mode [20][21][22]62] and the 17 THz apical mode [63]. These experimental pursuits will be vital for theories examining the complex interactions underlying high temperature superconductivity.…”
mentioning
confidence: 99%
“…In the underdoped region, the normal state deviates significantly from the Fermi liquid behaviors and the superconducting gap is particularly anomalous: it decreases with increasing doping even though T c still increases with doping, and the measured momentumdependent superconducting gap deviates more obviously from the standard d-wave form with decreasing doping [1,2,4,5]. In the overdoped region, on the other hand, the normal state properties appear to become close to a Fermi liquid while the superconducting gap tends to resemble the BCS behaviors: it decreases with increasing doping with a concomitant T c decrease and its momentum dependence follows a standard d-wave form [1,2,5,6]. It has been also found that superconductivity of the cuprate superconductors is sensitive to the number of CuO 2 planes, n, in one structural unit; T c increases from single-layer (n=1), to bilayer (n=2) and trilayer (n=3), reaches a maximum for trilayer (n=3), and then drops with the further increase of the number of CuO 2 planes [7][8][9].…”
mentioning
confidence: 99%
“…It has been also found that superconductivity of the cuprate superconductors is sensitive to the number of CuO 2 planes, n, in one structural unit; T c increases from single-layer (n=1), to bilayer (n=2) and trilayer (n=3), reaches a maximum for trilayer (n=3), and then drops with the further increase of the number of CuO 2 planes [7][8][9]. Investigations on the doping dependence and CuO 2 layer dependence of the electronic structure and superconducting gap symmetry are important for understanding the origin of high temperature superconductivity in cuprate superconductors Angle-resolved photoemission spectroscopy (ARPES) measurements on Bi 2 Sr 2 CaCu 2 O 8+δ (Bi2212) have provided major results on the doping and temperature evolutions of electronic structure, many-body effects, peudogap and superconducting gap about cuprate superconductors [1,2,5,6,10,11] because Bi2212 is easy to cleave to get smooth sample surface for ARPES measurements and can cover a relatively wide range of doping levels. In fact, Bi2212 consists of two CuO 2 planes in one structural unit separated by calcium (Ca).…”
mentioning
confidence: 99%